The STARS Phase 2 Study: A Randomized Controlled Trial of Gaboxadol in Angelman Syndrome. (16th February 2021) - Bird, Lynne M.; Ochoa-Lubinoff, Cesar; Tan, Wen-Hann; Heimer, Gali; Melmed, Raun D.; Rakhit, Amit; Visootsak, Jeannie; During, Matthew J.; Holcroft, Christina; Burdine, Rebecca D.; Kolevzon, Alexander; Thibert, Ronald L.
Abstract : Objective: To evaluate safety and tolerability and exploratory efficacy end points for gaboxadol (OV101) compared with placebo in individuals with Angelman syndrome (AS). Methods: Gaboxadol is a highly selective orthosteric agonist that activates δ-subunit–containing extrasynaptic γ-aminobutyric acid type A (GABAA ) receptors. In a multicenter, double-blind, placebo-controlled, parallel-group trial, adolescent and adult individuals with a molecular diagnosis of AS were randomized (1:1:1) to 1 of 3 dosing regimens for a duration of 12 weeks: placebo morning dose and gaboxadol 15 mg evening dose (qd), gaboxadol 10 mg morning dose and 15 mg evening dose (bid), or placebo morning and evening dose. Safety and tolerability were monitored throughout the study. Prespecified exploratory efficacy end points included adapted Clinical Global Impression–Severity and Clinical Global Impression–Improvement (CGI-I) scales, which documented the clinical severity at baseline and change after treatment, respectively. Results: Eighty-eight individuals were randomized. Of 87 individuals (aged 13–45 years) who received at least 1 dose of study drug, 78 (90%) completed the study. Most adverse events (AEs) were mild to moderate, and no life-threatening AEs were reported. Efficacy of gaboxadol, as measured by CGI-I improvement in an exploratory analysis, was observed in gaboxadol qd vs placebo ( p = 0.0006). Conclusion: After 12 weeks of treatment, gaboxadol was found to be generally well-tolerated with a favorable safety profile. The efficacy as measured by the AS-adapted CGI-I scale warrants further studies. Clinicaltrials.gov Identifier: NCT02996305. Classification of Evidence: This study provides Class I evidence that, for individuals with AS, gaboxadol is generally safe and well-tolerated.